2022
DOI: 10.1038/s41531-021-00276-6
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and roadmap of novel neuromodulation targets for treatment of gait in Parkinson’s disease

Abstract: Gait issues in Parkinson’s disease (PD) are common and can be highly disabling. Although levodopa and deep brain stimulation (DBS) of the subthalamic nucleus and the globus pallidus internus have been established therapies for addressing the motor symptoms of PD, their effects on gait are less predictable and not well sustained with disease progression. Given the high prevalence of gait impairment in PD and the limitations in currently approved therapies, there has been considerable interest in alternative neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…However, consistent with our results, some stages utilize more diffuse connectivity, in which each microchannel connects with all others typically at the level of to GPi/SNr (Shipp 2017). Clinical studies on Parkinson's disease (PD) patients has shown that deep brain stimulation (DBS) of the SNr but not of the Subthalamic nucleus (STN) was better at controlling anticipatory postural adjustments and gait control, and DBS has been shown to be feasible in PD patients with dyskinesia as well (Cury et al 2022). The implications of our result are that specifically focused therapeutic improvements towards the SNr, perhaps through the STN (Lagière et al 2020) could help in the plastic reorganization of the network to decrease the induction of repetitive oro-facial movements.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, consistent with our results, some stages utilize more diffuse connectivity, in which each microchannel connects with all others typically at the level of to GPi/SNr (Shipp 2017). Clinical studies on Parkinson's disease (PD) patients has shown that deep brain stimulation (DBS) of the SNr but not of the Subthalamic nucleus (STN) was better at controlling anticipatory postural adjustments and gait control, and DBS has been shown to be feasible in PD patients with dyskinesia as well (Cury et al 2022). The implications of our result are that specifically focused therapeutic improvements towards the SNr, perhaps through the STN (Lagière et al 2020) could help in the plastic reorganization of the network to decrease the induction of repetitive oro-facial movements.…”
Section: Discussionmentioning
confidence: 52%
“…Clinical studies on Parkinson’s disease (PD) patients has shown that deep brain stimulation (DBS) of the SNr but not of the Subthalamic nucleus (STN) was better at controlling anticipatory postural adjustments and gait control, and DBS has been shown to be feasible in PD patients with dyskinesia as well (Cury et al. 2022 ). The implications of our result are that specifically focused therapeutic improvements towards the SNr, perhaps through the STN (Lagière et al.…”
Section: Discussionmentioning
confidence: 99%
“…As for anxiety, Parkinson's anxiety scale (PAS) and a PD-specific anxiety scale have higher specificity and sensitivity for their use as a screening tools than other scales [27]. Non-pharmacologic approaches in Non-motor features in PD [25].…”
Section: Mood Disordersmentioning
confidence: 99%
“…Despite good results of SCS in treating gait problems, only a small number of PD patients were evaluated so far, with variable study populations. Furthermore, the stimulation produces tangible sensations which might be responsible for a placebo effect, which should be addressed in newer trials 69 . Double-blind approaches designed with an amplitude subthreshold for paresthesia, very high frequencies (below the sensory threshold), or new paradigms such as burst stimulation, will hopefully guide these future trials to avoid placebo effects 70 .…”
Section: New Targetsmentioning
confidence: 99%